2006
DOI: 10.1098/rstb.2006.1932
|View full text |Cite
|
Sign up to set email alerts
|

Social odours, sexual arousal and pairbonding in primates

Abstract: We describe the role of social odours in sexual arousal and maintaining pairbonds in biparental and cooperatively breeding primates. Social odours are complex chemical mixtures produced by an organism that can simultaneously provide information about species, kinship, sex, individuality and reproductive state. They are long lasting and have advantages over other modalities. Both sexes are sensitive to changes in odours over the reproductive cycle and experimental disruption of signals can lead to altered sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 45 publications
1
31
0
1
Order By: Relevance
“…Aggression is closely associated with mating and inter-individual social hierarchies in most animal models (Lorenz 1966;Wilson 1975;Hemelrijk and Kunz 2004;Brennan and Kendrick 2006;Snowdon et al 2006;Scordato and Drea 2007;Hemelrijk et al 2008), and many of these models strongly implicate HLA as a detectable, selective force (Lewis 1998;Eggert et al 1999a;Landry et al 2001;Hambuch and Lacey 2002;Yamazaki et al 2002;Milinski et al 2005;Petfield et al 2005;Brennan and Kendrick 2006). Based upon this evidence, Kohl et al (2001) suggested new approaches to studying MHC-based pheromonal recognition among humans and mammals, including precise measurements of individual HLA genotypes among interacting individuals, considerations of varying biochemistries, changes in physiological status, and human microbial flora.…”
Section: Introductionmentioning
confidence: 99%
“…Aggression is closely associated with mating and inter-individual social hierarchies in most animal models (Lorenz 1966;Wilson 1975;Hemelrijk and Kunz 2004;Brennan and Kendrick 2006;Snowdon et al 2006;Scordato and Drea 2007;Hemelrijk et al 2008), and many of these models strongly implicate HLA as a detectable, selective force (Lewis 1998;Eggert et al 1999a;Landry et al 2001;Hambuch and Lacey 2002;Yamazaki et al 2002;Milinski et al 2005;Petfield et al 2005;Brennan and Kendrick 2006). Based upon this evidence, Kohl et al (2001) suggested new approaches to studying MHC-based pheromonal recognition among humans and mammals, including precise measurements of individual HLA genotypes among interacting individuals, considerations of varying biochemistries, changes in physiological status, and human microbial flora.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, research on olfaction has lagged behind other sensory modalities [Semple and Higham, 2013;Drea, 2015]. One well-studied species, common marmoset monkeys (Callithrix jacchus), use scent in a variety of social contexts including individual identification [Smith, 2006], intragroup communication [Ziegler et al, 2005], and sexual signaling [Snowdon et al, 2006]. However, less is known regarding the ecological contexts in which marmosets use olfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Scents are an essential mechanism of communication in primates, even for lineages with a reduced sense of smell [Snowdon et al, 2006;Semple and Higham, 2013]. Despite this, research on olfaction has lagged behind other sensory modalities [Semple and Higham, 2013;Drea, 2015].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The review also provides insights into the nature of learning-induced changes which occur within these systems in both rodent mate recognition and sheep models of offspring recognition. The second review focuses on a recent series of brain imaging studies on pair-bonding marmosets revealing that social odours which signal reproductive state influence not only sexual arousal and brain regions mediating the sexual response, but also those associated with memory and emotional decision making as well (Snowdon et al 2006). This paper also discusses evidence for similar roles of social odours in the control of human reproduction, although it is clear that odour plays less of a role in humans than in many other species.…”
mentioning
confidence: 99%